NEGATIVE ATTITUDES IN SIDNEY SHELDON’S NOVEL THE BEST LAID PLANS - Luna Rezki Dafnari; Devi Pratiwy (JOURNAL OF LANGUAGE, 2019)
This research analyses the negative attitudes of the protagonist in The Best Laid Plans written by an American novelist, Sidney Sheldon. The novel tells the revenge of the selfish and ambitious protagonist Leslie Stewart who has been so obsessed with destroying Oliver's reputation for betraying him. Leslie is the most fascinating figure in the whole course of the story between his selfish and ambitious attitude and his madness. She feels that she has been neglected and cast away and this hardens his heart, until she does not care about the feelings of others. This phenomena is compatible with a theory of selfish in which it is stated that When talking, he does not care about the feelings of others. If there is a division of something he is selfish. He never thought that his actions caused many people to be harmed (Poniman, 2007). This research adopts qualitative method supported by relevant theories, one of which is proposed by Creswell (2009). The result reveals that there are two dominant attitudes emerging from the analysis, those are selfish and ambitious.